A THEORETICAL ANALYSIS OF THE NEW POLISH INCOME TAX SYSTEM - Urszula Król (Copernican Journal of Finance & Accounting, 2023)
The research objective of this article is to present changes incorporated into the Polish income tax system and their potential influence on entrepreneurs’ behaviour. One of the most important features of the income taxation system for Polish entrepreneurs is that they can choose the rules of taxation. Under certain conditions, they can apply a progressive scale tax, a flat tax, or a revenue-based tax. The changes introduced in the year 2022 mean that for many entrepreneurs, the burden of taxation has increased. The theoretical and model analysis presented in this article revealed that for many of them, the revenue-based tax has become (or always has been) the optimal form of taxation. The analysis also indicates a serious problem with this form of taxation in the context of equity. This study may provide a basis for further research on the impact of tax perturbations on business activity, business structure, and costs of compliance.